The Effect of Ethnic Clustering on Migrant Integration in Germany - Sandra Schaffner; Barbara Treude (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
Since ethnic clustering is common in Germany, a better understanding of its effects on the integration of immigrants could be important for integration policies, especially in the light of rising immigration and a skilled worker shortage. Yet, both economic theory and empirical research for other countries cannot give a clear-cut answer to whether clustering is benefi cial or detrimental for immigrants' integration. In this paper, the effect of residential clustering on the labour market outcome of first-generation immigrants in Germany is analysed empirically. It, thus, contributes to the literature by extending it to Germany on which hardly any research has been conducted. For the analysis, two measures for labour market integration are used: the employment probability and wage levels. In order to control for the endogeneity of the location decision, a two-step strategy is used, combining a control function and an instrumental variable (IV) approach. The results suggest a negative enclave effect on both employment and wages, that is even larger when sorting is taken into account. – – Im Zuge stärkerer Einwanderung nach Deutschland und drohendem Fachkräftemangel ist die Integration von Immigranten von großer Bedeutung. Hier lässt sich häufig beobachten, dass Migranten gleicher oder ähnlicher Herkunft gemeinsam in der gleichen Nachbarschaft wohnen. Sowohl die ökonomische Theorie als auch andere empirische Arbeiten geben keinen eindeutigen Hinweis darauf, ob diese ethnische Segregation förderlich oder hinderlich für die Integration von Migranten ist. Insbesondere für Deutschland existiert bisher kaum Evidenz zu dieser Fragestellung. In diesem Papier wird der Effekt ethnischer Segregation auf den Arbeitsmarkterfolg von Migranten analysiert. Dabei wird der Arbeitsmarkterfolg als Erwerbsbeteiligung zum einen und als Lohnniveau zum anderen definiert. Um für mögliche Endogenität der Wohnortwahl zu kontrollieren, wird eine zweistufige Vorgehensweise aus einer Kontrollfunktion und einem Instrumentvariablenansatz gewählt. Die Ergebnisse zeigen, dass es einen negativen Effekt der ethnischen Segregation sowohl auf die Erwerbsbeteiligung als auch das Lohnniveau gibt. Dieser Effekt ist sogar größer, wenn für die Endogenität der Wohnortwahl kontrolliert wird.
Keywords: J61; J64; J31; R23; 330; ethnic enclaves; residential clustering; labour market integration; migrants; wage differentials